A dominant TRPV4 variant underlies osteochondrodysplasia in Scottish fold cats. Issue 8 (August 2016) - Gandolfi, B.; Alamri, S.; Darby, W.G.; Adhikari, B.; Lattimer, J.C.; Malik, R.; Wade, C.M.; Lyons, L.A.; Cheng, J.; Bateman, J.F.; McIntyre, P.; Lamandé, S.R.; et al.
Summary: Objective: Scottish fold cats, named for their unique ear shape, have a dominantly inherited osteochondrodysplasia involving malformation in the distal forelimbs, distal hindlimbs and tail, and progressive joint destruction. This study aimed to identify the gene and the underlying variant responsible for the osteochondrodysplasia. Design: DNA samples from 44 Scottish fold and 54 control cats were genotyped using a feline DNA array and a case–control genome-wide association analysis conducted. The gene encoding a calcium permeable ion channel, transient receptor potential cation channel, subfamily V, member 4 ( TRPV4 ) was identified as a candidate within the associated region and sequenced. Stably transfected HEK293 cells were used to compare wild-type and mutant TRPV4 expression, cell surface localisation and responses to activation with a synthetic agonist GSK1016709A, hypo-osmolarity, and protease-activated receptor 2 stimulation. Results: The dominantly inherited folded ear and osteochondrodysplasia in Scottish fold cats is associated with a p.V342F substitution (c.1024G>T) in TRPV4 . The change was not found in 648 unaffected cats. Functional analysis in HEK293 cells showed V342F mutant TRPV4 was poorly expressed at the cell surface compared to wild-type TRPV4 and as a consequence the maximum response to a synthetic agonist was reduced. Mutant TRPV4 channels had a higher basal activity and an increased response to hypotonic conditions. Conclusions: Access to a naturally-occurring TRPV4 mutation in the Scottish fold cat will allow further functional studies to identify how and why the mutations affect cartilage and bone development.